Da borda de uma escrita alterada: o corte na rota turística - Restelatto, Mônica (My University, 2020)
The present work problematizes the meaning-effect the tourist route of the "most italian city of Brazil". The theoretical-analytical and methodological device was the Pecheutian Discourse Analysis interfaced with Psychoanalysis, Tourism and Art. The materiality of analysis are the corn straw dolls, handcrafted, and sold as a souvenir on the tourist route in Antônio Prado-RS. The formulation of the tourist route produces the crystallization of some senses, to the detriment of other destabilizing knowledge. The concepts of heritage, preconstructed, memory and repetition ere mobilized to support the analysis. The dolls are part of the heritage apparatus that elevates and frames the preconstructed meritocratic discourse of the Italian immigration memory. The production of this work led to another form of presentation of scientific knowledge. The box is the support of such proposal, commitment to the reverse as to the obligation of the text typing format as the only possible product of the completion of a master's degree. The box contains artisanal artifacts that testify to the process of elaborating the (dis)route in a fragmentary approach [resumo fornecido pelo aluno].
O presente trabalho problematiza o efeito de sentido da rota turística da "cidade mais italiana do Brasil". O dispositivo teórico-analítico e metodológico é o da Análise do Discurso pecheutiana em interface com a Psicanálise, Turismo e Arte. A materialidade de análise são as bonecas de palha de milho, produzidas artesanalmente, e comercializadas como souvenir na rota turística no município de Antônio Prado/RS. A formulação da rota turística produz a cristalização de alguns sentidos, em detrimento a outros saberes em desestabilização. Os conceitos de patrimônio, pré-construído, memória e repetição são mobilizados para embasar a análise. As bonecas são parte do aparato patrimonial que enaltece e emoldura o discurso meritocrata pré-construído da memória da imigração italiana. A produção deste trabalho suscita outra forma de apresentação do conhecimento científico. A caixa é o suporte de tal proposta, compromisso ao reverso quanto à obrigatoriedade do formato de digitação de texto como único produto possível da conclusão de um mestrado. A caixa contém artefatos de construção artesanal que testemunham o processo de elaboração da (des)rota em abordagem fragmentária [resumo fornecido pelo aluno].
Keywords: Turismo - Antônio Prado (RS); Análise de discurso; Memória coletiva; Patrimônio cultural; Tourism - Antônio Prado (Brazil); Discourse analysis; Collective memory; Cultural heritage